Dental Prophylaxis and Osteoradionecrosis: A Population-Based Study. (May 2017) - Chang, C.T.; Liu, S.P.; Muo, C.H.; Tsai, C.H.; Huang, Y.F.
The aim of this study was to investigate the association of different dental prophylactic modalities and osteoradionecrosis (ORN) and determine the risk of ORN under different timing periods of scaling, with the use chlorhexidine mouth rinse after surgery and with different strategies of fluoride gel application in head and neck cancer (HNC) participants. A cohort of 18, 231 HNC participants, including 941 ORN patients and 17, 290 matched control cases, were enrolled from a Longitudinal Health Insurance Database for Catastrophic Illness Patients (LHID-CIP) in Taiwan. Based on different dental prophylactic modalities before radiotherapy, including chlorhexidine mouth rinse, scaling, and fluoride gel, all HNC subjects were stratified into different groups. The Cox proportional hazard regression was used to compare ORN incidences under different dental prophylactic modalities. The results revealed that scaling and chlorhexidine mouth rinse were significantly related to ORN risk ( P = 0.004 and P < 0.0001). Chlorhexidine mouth rinse was highly correlated to ORN occurrence (hazard ratio [HR], 1.83–2.66), as exposure increased the risk by 2.43-fold among oral cancer patients, regardless of whether they had received major oral surgery or not. Oral cancer patients receiving scaling within 2 wk before radiotherapy increased their incidence of ORN by 1.28-fold compared with patients who had not undergone scaling within 6 mo. There is no significance of fluoride application for dental prophylaxis in increasing ORN occurrence. In conclusion, dental prophylaxis before radiotherapy is strongly correlated to ORN in HNC patients. Chlorhexidine exposure and dental scaling within 2 wk before radiotherapy is significantly related to ORN risk, especially in oral cancer patients. The use of 1.1% NaF topical application did not significantly increase the risk of ORN in HNC patients. An optimal dental prophylaxis protocol to reduce ORN should concern cancer location, cautious prescription of chlorhexidine mouth rinse, and proper timing of scaling.